Strikes as the Random Enforcement of Asymmetric Information Contracts - Leach, John (Journal of Labor Economics, 1992)
A two-state model of strikes, in which both the entrepreneur and the worker randomize their behavior, is developed. The entrepreneur always asks for a wage reduction unaccompanied by a cut in labor services if the state is bad, and he sometimes makes the same request in the good state. The worker sometimes agrees to this request and sometimes threatens to strike. The strike threat is only carried out in the bad state. This equilibrium can Pareto dominate that found in the standard asymmetric information contracting model.